'Because they believed': Students' ideas of historical empathy in Greek Cypriot primary education. Issue 2 (17th October 2019) - Perikleous, Lukas
What happened in the past is often the result of human behaviour (individual or collective) that was guided by certain ideas, beliefs and intentions, and influenced by the historical context in which it happened. It can be argued that understanding past behaviour is essential for historical understanding, and therefore students' ideas about making sense of people in the past are important for history education. This article reports on aspects of a broader qualitative study of students' and teachers' ideas of historical empathy. More specifically, the study explores participants' reasoning in terms of the ideas they use to explain the behaviour of groups of people in the past and the present. The sample was drawn from two urban primary schools in Nicosia, Cyprus; 68 students, aged between 8 and 12, and five history teachers in the sample classes participated in it. Pen-and-paper tasks, semi-structured interviews and classroom observations were used as data generation instruments. This article focuses on some of the findings of the analysis of students' responses to pen-and-paper tasks, which asked them to explain religious practices for the treatment of diseases used by two different groups in the past. These findings suggest the existence of ideas of historical empathy identified by previous studies. In this sense, they contribute to the existing evidence of the presence of these ideas in a variety of educational and cultural contexts.